Instrument constituencies and the brokering of OECD-knowledge in Nordic school reforms - a three country comparison - Kirsten Sivesind; Andreas Nordin; Christian Ydesen (Taylor & Francis Group, 2024)
Major international surveys and reports have considerably altered the expectations and outlooks of national policymakers in education over the last three decades. Through a comparative content analysis of bibliographies in policy documents, this article explores the intermediary bodies that facilitate salient interconnections between international organizations such as the Organization for Economic Cooperation and Development (OECD) and national policymakers and experts who prepare comprehensive school reforms in three Nordic countries: Denmark, Norway and Sweden. This article builds on a large Nordic research project that studied the transfer and translation of international policies in a Nordic reform context. It extends the study by examining the role of publishers as intermediary policy brokers that legitimize the usage of OECD knowledge as significant members of instrument constituencies. This study enhances our understanding of the variations in citation patterns across policy documents from three Nordic countries. It also investigates the extent to which differences in instrumental constituencies arise from institutional arrangements and the ideational foundations underpinning reform trajectories. Additionally, it examines the topics addressed by these reforms and the governments' affiliations with new policy brokers supported by both public and private publishers.